2018
DOI: 10.1371/journal.pone.0206831
|View full text |Cite
|
Sign up to set email alerts
|

Critically ill healthcare workers with the middle east respiratory syndrome (MERS): A multicenter study

Abstract: BackgroundMiddle East Respiratory Syndrome Coronavirus (MERS-CoV) leads to healthcare-associated transmission to patients and healthcare workers with potentially fatal outcomes.AimWe aimed to describe the clinical course and functional outcomes of critically ill healthcare workers (HCWs) with MERS.MethodsData on HCWs was extracted from a multi-center retrospective cohort study on 330 critically ill patients with MERS admitted between (9/2012–9/2015). Baseline demographics, interventions and outcomes were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 24 publications
1
32
0
1
Order By: Relevance
“…Nosocomial transmission to other patients and transmission to HCWs has been a major feature of both outbreaks of SARS, MERS and now COVID-19 [15,21]. In one report, 41% of hospitalized COVID-19 cases were acquired in hospital, including patients who were already hospitalized for other reasons and healthcare workers [15].…”
Section: Infection Prevention and Controlmentioning
confidence: 99%
“…Nosocomial transmission to other patients and transmission to HCWs has been a major feature of both outbreaks of SARS, MERS and now COVID-19 [15,21]. In one report, 41% of hospitalized COVID-19 cases were acquired in hospital, including patients who were already hospitalized for other reasons and healthcare workers [15].…”
Section: Infection Prevention and Controlmentioning
confidence: 99%
“…Fever at presentation, was found in 30/32 (93.8%), cough in 25/32 (78.1%), and gastrointestinal symptoms in11/32 (34.4%). Eight out of the 32 (25%) healthcare workers died (Shalhoub et al, 2018).…”
Section: Severe Mers Pneumonia Among Healthcare Workersmentioning
confidence: 99%
“…In one case-control study of patients with MERS, the rescue use of ECMO compared to a matched control with no-ECMO was associated with reduced in-hospital-mortality (65% compared 100%) (Alshahrani et al, 2018). Another retrospective study, found that critically ill healthcare workers who died because of MERS were more likely to have received ECMO than not, probably because the severity of pneumonia that led to use of rescue therapy, rather than use of ECMO itself (Shalhoub et al, 2018). Corticosteroids have been used frequently in MERS patients.…”
Section: Supportive Therapymentioning
confidence: 99%
“…Ribavirin and interferon α2b treatment produced promising preclinical data in rhesus macaques, including moderate reductions in viral load and partially effective prevention of progression to pneumonia when infected animals were compared with untreated infected controls (Falzarano et al, 2013). However, data on MERS-CoV infected patients treated with a combination of ribavirin and interferon (either α2a or β1) have been inconsistent depending on the statistical analysis methods used to compare the datasets (Al Ghamdi et al, 2016;Al-Tawfiq et al, 2014;Omrani et al, 2014;Shalhoub et al, 2018). The largest study that adjusted for time-varying confounders that might influence the decision to initiate ribavirin and interferon therapy did not show an improvement in mortality (Arabi et al, 2017a).…”
Section: Clinical Management Of Middle East Respiratory Syndrome (Mers)mentioning
confidence: 99%